Study on the Effects of Liquid Thermal Media on the Irradiation Capsule of High-Temperature Materials - Man Soon Cho; Sung Ryul Kim; Seong Woo Yang; Kee Nam Choo (Science and Technology of Nuclear Installations)
Irradiation tests of materials at HANARO have usually been conducted using a standard capsule at temperatures of about 300°C for irradiation of materials used at PWR. Thus, the standard capsule uses aluminum as the specimen holder, which acts to dissipate the thermal energy. Future nuclear systems such as a VHTR and SFR require the irradiation tests at a relatively high temperature. As an alternative to aluminum which has been used as the thermal media in a standard material capsule, the characteristics of liquid metals such as NaK and LBE are reviewed. The temperatures of the capsule are affected by the variation of parameters such as the gap and wall thickness of the container. In particular, the external gap is most important in determining the temperature of the specimen. LBE raises the temperature of the specimen higher than NaK at the same configuration of the capsule. Thus, LBE can lessen the gap of the parts and reduce the vibration for a stable long-term test in reactor.